2012
DOI: 10.17221/6339-pse
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and phosphorus resorption of Artemisia scoparia, Chenopodium acuminatum, Cannabis sativa, and Phragmites communis under nitrogen and phosphorus additions in a semiarid grassland, China

Abstract: A factorial nitrogen (N) × phosphorus (P) addition experiment was conducted to evaluate responses of leaf nutrient resorption to increased soil N and P availability in a semiarid grassland in Keerqin Sandy Lands, China. Four plant species were selected, among which Artemisia scoparia and Chenopodium acuminatum were dominant species in the control and P-added plots, and Cannabis sativa and Phragmites communis were dominant in the N-and N + P-treated plots. Results showed that N and P resorption varied substanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Longterm N additions to a boreal peatland increased P resorption efficiencies in two evergreen shrubs (Wang et al 2014). Nitrogen fertilization in grasslands caused increased P resorption efficiency in some species but not others in Mongolia (Li et al 2012) and in northeastern China (Lu and Han 2010). In the latter study, soil P concentrations did not differ significantly from controls, suggesting that the observed changes in P resorption were not caused by decreased soil P availability following N addition.…”
Section: Discussionmentioning
confidence: 96%
“…Longterm N additions to a boreal peatland increased P resorption efficiencies in two evergreen shrubs (Wang et al 2014). Nitrogen fertilization in grasslands caused increased P resorption efficiency in some species but not others in Mongolia (Li et al 2012) and in northeastern China (Lu and Han 2010). In the latter study, soil P concentrations did not differ significantly from controls, suggesting that the observed changes in P resorption were not caused by decreased soil P availability following N addition.…”
Section: Discussionmentioning
confidence: 96%
“…C gain efficiency decreased quadratically with increasing P input, which also supported this assumption. The possible explanation for the observed logarithmic relationship is that P absorption proficiency of plant species decreased in response to P addition intensities[32]. Niu et al [33] reported that P addition has no apparent effect on net ecosystem exchange in temperate steppe.…”
Section: Discussionmentioning
confidence: 99%
“…2). First, a greater fraction of foliar N and P are resorbed in nutrient-poor soil-plant systems (Aerts 1996, Richardson et al 2005, Silla and Escudero 2006, Li et al 2012, Lu et al 2012. Second, N:P resorption ratios generally increase when the soil is N limited and generally decrease when the soil is P limited (van Heerwaarden et al 2003, Zotz 2004).…”
Section: Factors Determining the Differences In N And P Concentrationmentioning
confidence: 99%